Rendering South Africa Undesirable : A Critique of Refugee and Informal Sector Policy - Crush, Jonathan, 1953-; Stulgaitis, Manal; Skinner, Caroline (Migration policy series, 2018)
To understand the policy environment within which refugees establish and operate their enterprises in South Africa's informal sector, this report brings together two streams of policy analysis. The first concerns the changing refugee policies and the erosion of the progressive approach that characterized the immediate post-apartheid period. The second concerns the informal sector policy, which oscillates between tolerance and attempted destruction at national and municipal levels. While there have been longstanding tensions between foreign and South African informal sector operators, an overtly anti-foreign migrant sentiment has increasingly been expressed in official policy and practice. This report describes the strategies being used to turn South Africa into an undesirable destination for refugees, including the setting up of additional procedural, administrative and logistical hurdles; the undercutting of court judgments affirming the right of asylum-seekers and refugees to employment and self-employment; ensuring that protection is always temporary by making it extremely difficult for refugees to progress to permanent residence and eventual citizenship; and restricting opportunities to pursue a livelihood in the informal sector. The authors conclude that the protection of refugee rights is likely to continue to depend on a cohort of non-governmental organizations prioritizing migrant livelihood rights and being willing and able to pursue time-consuming and costly litigation on their behalf.